An empirical analysis of the dynamics of the welfare state : the case of benefit morale - Martin Halla; Mario Lackner; Friedrich G. Schneider (Center for Economic Studies and ifo Institute (CESifo), 2009)
Does the supply of a welfare state create its own demand? Many economic scholars studying welfare arrangements refer to Say's law and insinuate a self-destructive welfare state. However, little is known about the empirical validity of these assumptions and hypotheses. We study the dynamic effect of different welfare arrangements on benefit fraud. In particular, we analyze the impact of the welfare state on the respective social norm, i.e. benefit morale. It turns out that a high level of public social expenditures and a high unemployment rate are associated with a small positive (or no) immediate impact on benefit morale, which however is crowded out by adverse medium and long run effects.
Keywords: A13; I30; I38; J65; J68; H20; Z13; 330; welfare state; social norms; benefit fraud; benefit morale; Sozialstaat; Öffentliche Sozialausgaben; Soziale Norm; Sozialhilfe; Betrug; Arbeitslosigkeit; Europa; Industriestaaten